Penerapan Manajemen Berbasis Madrasah dalam Meningkatkan Mutu Pembelajaran Akidah Akhlak di MIN 3 Pekanbaru - Wahyu (UNISAN JURNAL, 2024)
This research aims to explore the application of madrasa-based management in improving the quality of moral teachings at Madrasah Ibtidaiyah Negeri (MIN) 3 Pekanbaru. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with madrasa heads, teachers and administrators as well as direct observation in learning classes. The results of the research show that the implementation of madrasa-based management has a significant positive impact on the quality of moral teachings at MIN 3 Pekanbaru. Madrasah-based management helps improve coordination between madrasa administrators, teachers and other stakeholders, which in turn increases the efficiency and effectiveness of the learning process. Apart from that, the implementation of madrasa-based management also allows the development of a curriculum that suits students' needs as well as the implementation of innovative and relevant learning methods. With madrasa-based management, decision making becomes more planned and directed, thus facilitating the achievement of learning goals more effectively. These findings provide an important contribution to the development of Islamic education in Indonesia, especially in the context of learning moral beliefs in madrasas. The practical implication of this research is the importance of strengthening the implementation of madrasa-based management as an effort to continue to improve the quality of Islamic religious education in formal educational institutions. Further research can expand the scope to see the impact of implementing madrasa-based management in the context of learning other subjects in madrasas.